The Correlation of Resilience and Anxiety in the Candidate Burn Patients for Skin Grafting - M Seyedoshohadaee; A Seraj; H Haghani (Iran University of Medical Sciences, 2020)
Background & Aims: Victims of burn injuries experience numerous psychological complications, including anxiety. Preoperative anxiety is rather common and normal, and resilience is considered to be an effective coping strategy in stressful situations. The present study aimed to assess the correlation between resilience and anxiety in the candidate burn patients for skin grafting. Materials & Methods: This cross-sectional, descriptive-correlational study was conducted via continuous sampling and based on the inclusion criteria. Data were collected using Beck anxiety inventory and CD-RISC, which were completed 20-30 minutes before the surgery at the inpatient ward in July 2019. Data analysis was performed in SPSS version 16 using descriptive and inferential statistics in the form of tables and numerical indicators. To achieve the research objectives and answer the research questions, the analysis of variance (ANOVA), independent t-test, and Pearson's correlation-coefficient were also used. Results: In total, 66.2% of the patients had higher resilience scores than 50. The mean scores of resilience and anxiety were 64.57±22.25 and 12.88±10.45, respectively. A significant correlation was observed between resilience and anxiety, and the increased score of resilience was associated with decreased anxiety (r=0.81; P<0.001). Resilience was significantly correlated with education level (P<0.001), economic status (P=0.001), occupation status (P=0.02), and place of residence (P=0.035). In addition, anxiety was significantly correlated with education level (P=0.004), economic status (P=0.011), occupation status (P=0.03), and place of residence (P=0.016). Conclusion: According to the results, resilience and anxiety were correlated, and higher resilience was associated with lower anxiety. Furthermore, the candidate burn patients for skin grafting had mild anxiety and moderate resilience. Therefore, resilience training is recommended for the reduction of anxiety in these patients before surgery.